(untitled) (KYAMC Journal, 2026)
Background: Sodomy, or non-consensual anal intercourse, is a legally and socially sensitive issue in Bangladesh, often underreported due to stigma and criminalization under Section 377 of the Penal Code. Forensic investigation of such cases is limited, especially for male and transgender victims. This study reviews the forensic patterns, practices, and challenges associated with sodomy cases reported in 2024. Materials and Methods: A retrospective analysis was conducted on 71 medico-legal sodomy cases documented across 15 health institutions in Bangladesh between January and December 2024. Data included demographic details, injury patterns, forensic findings, time of reporting, and perpetrator relationship. A comparative literature review was undertaken for contextual discussion. Results: Of the 71 cases, 83.1% involved male victims and 16.9% transgender individuals, with 85.9% being minors. Anal injuries were present in 85.9% of cases, predominantly abrasions and tears. Only 12.7% of cases had positive semen detection, mainly among those reported within 24 hours. Most assaults (71.8%) were committed by known individuals. Delayed reporting (over 72 hours in 63% of cases) significantly reduced the forensic yield. Conclusion: Reform is urgently needed in forensic procedures, legal interpretation of Section 377, and victim support systems to improve justice for sodomy survivors in Bangladesh.